STUDENTS’ PERCEPTIONS TOWARD POSTGRADUATE STUDY: A PRELIMINARY INVESTIGATION - Teoh Sian Hoon; Geethanjali Narayanan; Gurnam Kaur Sidhu; Lim Peck Choo; Chan Yuen Fook; Nur Nisa Batrisyia Md Salleh (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Despite the sharp increase in postgraduate enrolments, universities have been overwhelmed with problems of low completion rates among postgraduate students. The latest statistics revealed that the doctoral graduation rate is about 40% at a global level whilst only 12% managed to complete their studies on time from a public university in Malaysia in 2015. Today, postgraduate students’ ability to complete their studies on time has become one of the main concerns of universities. Universities place a lot of attention on graduating on time because it is one of the criteria for university ranking. When a student embarks on postgraduate study, his/her aim would be to graduate on time. However, there are many factors that contribute towards this aim. Thus, this preliminary study investigates students’ perception towards their postgraduate studies. It explores the skills acquired by the students and the challenges that they have faced thus far in the duration of their study. The sample for this investigation were 66 year one and year two postgraduate students in a public university in Malaysia. A quantitative survey research design was employed to explore postgraduates’ perspectives where data was collected using an adapted questionnaire. Initial findings revealed that the postgraduate students perceived, even though they were in the early stage of their study, they were moderately aware of the challenges they faced in their studies. Their greatest challenge was self-management followed by academic competencies. The least challenge they perceived was their emotional state. Meanwhile, the overall acquired skill among the postgraduate students was comparatively low. The students perceived their writing skill was the least acquired skill and the more acquired skills were the conceptual and critical reading skills.